The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jcpp.13083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a behavioral intervention, delivered by pediatricians or psychologists, on sleep problems in children with ADHD: a cluster‐randomized, translational trial

Abstract: Background:We have demonstrated the efficacy of a brief behavioral intervention for sleep in children with ADHD in a previous randomized controlled trial and now aim to examine whether this intervention is effective and costeffective when delivered by pediatricians or psychologists in community settings. Methods: Translational, clusterrandomized trial of a behavioral intervention versus usual care from 19th January, 2015 to 30th June, 2017. Participants (n = 361) were children aged 5-13 years with ADHD and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Taking a different approach, directly treating sleep may lead to improvements in mood and emotion regulation. There is some evidence that improving sleep also improves emotional functioning in school‐aged children with ADHD (Hiscock et al, 2015; Keshavarzi et al, 2014; Sciberras et al, 2020), though improvements in emotional functioning were not found when a brief sleep intervention was delivered by community‐based clinicians (Hiscock et al, 2019). Studies have yet to evaluate evidence‐based cognitive‐behavioral sleep interventions in adolescents with ADHD, which will be important given the developmental changes and contexts that occur in adolescence that have implications for intervention delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Taking a different approach, directly treating sleep may lead to improvements in mood and emotion regulation. There is some evidence that improving sleep also improves emotional functioning in school‐aged children with ADHD (Hiscock et al, 2015; Keshavarzi et al, 2014; Sciberras et al, 2020), though improvements in emotional functioning were not found when a brief sleep intervention was delivered by community‐based clinicians (Hiscock et al, 2019). Studies have yet to evaluate evidence‐based cognitive‐behavioral sleep interventions in adolescents with ADHD, which will be important given the developmental changes and contexts that occur in adolescence that have implications for intervention delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an important clinical implication of the results is that ensuring sufficient sleep and avoiding conditions of sleep deprivation may be critical elements when addressing cognitive deficits related to ADHD. One way to achieve this goal is through a brief behavioral sleep intervention, such as CBT-i adjusted for ADHD, which has been shown to be effective at improving sleep problems in ADHD patients (Hiscock et al, 2019;Jernelöv et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings underscore the importance of examining both circadian preference and function in adolescents with ADHD. For some adolescents with ADHD and co-occurring sleep problems, sleep hygiene and behavioral interventions may be sufficient (e.g., Hiscock et al, 2019;Hiscock et al, 2015). However, if circadian factors contribute to, or exacerbate, sleep problems, more intensive interventions (e.g., Harvey et al, 2018) or circadian-specific interventions (e.g., bright light therapy) may be needed.…”
Section: Author Manuscriptmentioning
confidence: 99%
“…It is well-established that sleep problems and daytime sleepiness commonly co-occur with attention-deficit/hyperactivity disorder (ADHD) (Becker, 2020;Hiscock & Sciberras, 2019). Metaanalyses have demonstrated that school-aged children (Cortese, Faraone, Konofal, & Lecendreux, 2009) and adults (Díaz-Román, Mitchell, & Cortese, 2018) with ADHD are more likely than their peers without ADHD to have sleep problems, which independently contribute to poorer functioning (Sung, Hiscock, Sciberras, & Efron, 2008).…”
Section: Introductionmentioning
confidence: 99%